STUDI PERENCANAAN TEBAL RIGID PAVEMENT (STUDI KASUS PROYEK PEMBANGUNAN UNDERPASS KARANG SAWAH TONJONG BREBES) - Pingki Rakasiwi (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
This type of rigid pavement (Rigid Pavement) is an alternative to pavement in Indonesia which is currently widely used, because it is quite strong and lasts longer than flexible pavement. This is due to the heavy-loaded and high frequency lanes of vehicles operating on National, Arterial and Toll Roads.As in the Brebes area on Jalan Tegal - Purwokerto, it was reported that the volume of vehicles crossing the road was very high. This is exacerbated by the existing conditions of the roads that cross the railroad tracks so that the flow of transportation is not smooth and experiences congestion. Therefore, the Government built an underpass at the railway crossing in Karangsawah, Tonjong District, Brebes Regency, which is expected to be able to overcome the congestion that often occurs.Along with the economic growth in Indonesia which continues to develop and causes an increase in traffic flow. Especially in economic activities such as the distribution of goods and services between regions, provinces and the national level. For this reason, adequate facilities and infrastructure are needed so that these activities run smoothly. In order to support these activities, the government needs to allocate a large enough fund for road infrastructure.Road construction is one of the things that always goes hand in hand with technological advances and the thinking of the people who use it, because roads are an important facility for humans to reach the area they want to reach. Roads as a national transportation system have an important role, especially in supporting the economic, social, cultural and environmental fields developed through a regional development approach in order to achieve a balance and equitable development between regions.Keywords: Underpass Karang Sawah – Tonjong Brebes